Femtosecond laser inscribed superstructure fibre gratings - Kalli, Kyriacos; Davies, Edward M.; Komodromos, Michael; Webb, David J.; Zhang, Lin; Koutsides, Charalambos (My University, 2011)
We demonstrate the development of femtosecond laser inscribed superstructure fiber gratings (fsSFG) in silica optical fibre. We utilise a single step process, to inscribe low loss and polarisation independent, sampled gratings in optical fibres using the point by point femtosecond laser inscription method. Our approach results in a controlled modulated index change with complete suppression of any overlapping LPG structure leading to highly symmetric superstructure spectra, with the grating reflection well within the Fourier design limit. We also solve Maxwell's equations and calculate the back reflection spectrum using the bidirectional beam propagation method (BiBPM). Experimental results validate our numerical analysis and the estimation of inscription parameters such as ac index modulation, wavelength and the relative peak strength. We also explore how changes in the grating's period influence the reflection spectrum.
Keywords: Femtosecond lasers; Silica; Optical fibers; Fiber optics